Information sharing for effective IT incident resolving in IT service provider networks: a financial service case study. Issue 2 (30th December 2014) - Vlietland, Jan; Van Vliet, Hans
Abstract Information technology (IT)‐enabled financial services are typically delivered by a network of interdependent IT service providers. Such networks need information to resolve IT incidents in their delivered IT services. The objective of this research is to identify the set of information that needs to be visible within IT provider networks to effectively resolve IT incidents. To this end, we conducted an inductive case study in a network of nine interdependent IT service providers. We found that the required information is distributed over multiple technological stores, and operational IT staff in the network needs visibility over these technological stores. Operational staff also needs visibility over the social network of incident handling staff, given the tacit nature of the required information. We therefore premise that better information sharing and enhanced knowledge reuse in the service network has a positive impact on incident handling in IT service provider networks. The main contribution of this paper is a structured set of information types that positively impacts IT incident handling performance in the IT service network, packaged into a conceptual model. Copyright © 2014 John Wiley & Sons, Ltd.